The Role of Puppet Theaters in Educating the Young Generation in the Spirit of Love for the Fatherland - A’zamjon, Abdukhalilov (International Journal of Human Computing Studies, 2023)
The theater is a mirror of spirituality, a real center of education, and in its essence lies the important task of enriching the traditional world of human education and raising its culture. The fate of the nation, human life, country’s sorrow and joy should be reflected in such plays. A child’s mind looking at the world with joy is an example of white paper, and his heart is equally innocent. In this sense, the issue of upbringing is a process that requires careful thought, diligence and a deep mental approach. It is not appropriate to write or choose a work without taking into account the age of children, and clearly distinguishing the age group of the audience is the most important component. Puppet theater and theater art in general have special educational, ideological and aesthetic functions in the education of our young generation. The article talks about puppet theater and the attention paid to this field in Uzbekistan.